PEMBINAAN ADMINISTRASI PEMERINTAHAN DESA OLEH CAMAT BELIMBING DI KABUPATEN MUARA ENIM, SUMATERA SELATAN - Abdullah, Zet (PRAJA: Jurnal Ilmiah Pemerintahan, 2024)
The sub-district government is a level of government that has an important role in implementing services to the community, this then makes the sub-district head the spearhead in implementing general government tasks as well as some autonomous matters delegated by the Regent/Mayor to be implemented within the sub-district area. Government Regulation Number. 17 of 2018 Article 10 concerning Subdistricts, the government assigns subdistrict heads as heads of government to provide guidance in the administration of village government. One form of guidance that must be carried out by the sub-district government is to provide guidance on village government administration, because this is one of the activities that supports the implementation of good village government. From the background above, the author found the main problems including: First, how is village government administration developed by the Belimbing subdistrict head in Muara Enim Regency? Second, what are the obstacles to village government administration development by the Belimbing subdistrict head in Muara Enim Regency. The type of research used in writing this research is empirical legal research or survey, because it is oriented towards evaluating the implementation of general entertainment policies in the city of Palembang. This type of research is qualitative research, where qualitative research is research procedures that produce descriptive data in the form of written or spoken words from people and observable behavior directed at settings and individuals in a holistic (whole) manner. From the research results, development by the sub-district head of village government officials in a sub-district is needed to achieve orderly village government administration and an effective government system. This is based on the indicators used in this research, namely; Planning has been carried out optimally, guidance has been implemented. However, it has not yet run optimally, the briefing has been carried out. However, it has not yet run optimally, training has been carried out. However, it has not run optimally and the provision of guidelines has been carried out optimally. The obstacles faced by the Belimbing sub-district government are inadequate human resources owned by village officials and capabilities that are not in accordance with expertise in their field of work and the village government's delay in submitting accountability reports to the sub-district.